INTERNALISASI NILAI AKHLAK DAN KEDISIPLINAN BERBASIS AKSIOLOGI PENDIDIKAN ISLAM: Studi Kasus di Pondok Pesantren Tahfidz Putri Bustanul Mansyuriyah - Finta Nur Febriana; Abdul Khobir; Gojali (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2026)
This study examines how moral (akhlāq) values and discipline are internalized among female students through the axiological framework ofIslamic education at Bustanul Mansyuriyah Tahfidz Islamic Boarding School in Rowolaku, Kajen, Pekalongan Regency. Most prior studies connect Qur’an memorization (tahfidz) to character formation descriptively, without an explicit axiological lens distinguishing intrinsic and instrumental values, and rarely focus on female tahfidz pesantren whose students simultaneously pursue formal schooling and face digital-era distraction; this gap motivates the study. Guided by three questions concerning the axiologicalfoundation, the integration of tahfidz with character education, and the strategies and challenges of internalization, the research employs a qualitative case-study design. Data were collected through semi-structured in-depth interviews with purposively selected key informants, participatory observation of daily routines, and documentation, then analyzed thematically using the Miles–Huberman interactive model, with credibility strengthened through source triangulation, technique triangulation, and member checking. The findings reveal that internalization operates as an integrated system of exemplary modeling (uswah ḥasanah), habituation (taʼdīb), and educative sanction (taʼzīr), reinforced by a tightly scheduled tahfidz routine, layered supervision, and managed gadget use, so that discipline grows from internal awareness rather than mere formal compliance. The study contributes an empirically grounded value-mechanism-disposition model for character education in modern tahfidz pesantren.